The Holy Spirit in the New Testament a Pentecostal guide - Simmons, William A. 1954- (Westmont InterVarsity Press, 2021)
With an ever-increasing number of Christians worldwide self-identifying as Pentecostal or charismatic, the church needs a Spirit-centered interpretation of Scripture informed by a Pentecostal lens. In this accessible New Testament introduction, each chapter explores the presence of the Spirit in a biblical book, then offers devotional applications to help readers respond to the text.
Description based on publisher supplied metadata and other sources
Keywords: Electronic books